ROLE OF ARTIFICIAL INTELLIGENCE IN TRANSFORMING INDIAN HEALTHCARE - Bharti, Ankita; Kumari, Suman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the technological era, artificial intelligence is a tool that works like a human mind. There are many instances where AI is being put to good use, from hospitals and clinics to research facilities, academic work and labs. In terms of healthcare, AI facilitates examination and management of medical treatment. The success of AI systems in healthcare is due to the creation of complex algorithms that can pull valuable information from vast amounts of healthcare data. Auto-learning capabilities may be added to the algorithms to boost efficiency and precision. Artificial intelligence (AI) technologies provide doctors with sophisticated medical information from journals, clinical papers, and textbooks for quick patient treatment. AI has the potential to reduce human error in both diagnosis and treatment. Medical data, especially that relating to patients, may be used for the learning process. Biomarkers, NLP, expert systems based on rules, and physical robots are all examples of forms of AI that have applications in healthcare. Treatment planning, illness tracking, diagnostic help, and patient monitoring are all areas where AI has found use. This article aims to study the significance of AI in healthcare by looking at the different technologies used in India's Central Government Health Scheme (CGHS) and Ayushman Bharat health protection schemes to enhance the healthcare quality and patient satisfaction. In India, proper health screening is one of the most important things. So, learning how AI will affect healthcare services, professional practice, and infrastructure is essential.